Monetary Policy Transmission in Emerging Markets and Developing Economies - Brandao-Marques, Luis (IMF Working Papers; Working Paper ;, 2020)
Central banks in emerging and developing economies (EMDEs) have been modernizing their monetary policy frameworks, often moving toward inflation targeting (IT). However, questions regarding the strength of monetary policy transmission from interest rates to inflation and output have often stalled progress. We conduct a novel empirical analysis using Jorda's (2005) approach for 40 EMDEs to shed a light on monetary transmission in these countries. We find that interest rate hikes reduce output growth and inflation, once we explicitly account for the behavior of the exchange rate. Having a modern monetary policy framework-adopting IT and independent and transparent central banks-matters more for monetary transmission than financial development.